REDD Policy in Indonesia Reality in Grey Area - Bram, Deni (Department of Urban and Regional Planning, Diponegoro University, 2014)
Abstract: This note focuses on Reducing Emissions from Deforestation and Forest Degradation (REDD), an international framework that aims to curb carbon emissions by reducing deforestation. Meanwhile international negotiators discuss the environmental benefits of REDD, which will likely be implemented in the Kyoto Protocols post-2012 commitment period. Indonesia as one of countries with a high rate of deforestation and has large number of tropical forests of course become the main actor in REDD regime. Indonesia policy regarding REDD+ is the first come to response it in the regulation scope. Nowadays Indonesia has a lot of REDD+ project that based on voluntary approach and some of them are already finished. This condition makes the legitimacy of REDD+ regime in Indonesia to be questioned and seemed play in grey area because there is no legally binding formulation about REDD+ in international area but already exist in Ministry of Forestry level. This paper will emphasize some of the main issues related to REDD+ in international and Indonesia context. Firstly, the background on the adoption concept of REDD+ in international discourse and the debate from developed and developing countries perspective about it. Secondly, trace the basic legitimacy of REDD+ implementation in Indonesia based on regulations and stakeholder was involved in REDD+ project. Lastly, the response that should be done from the clearly position of REDD+ in Indonesia. This response was in order to encourage the legitimation of legal instrument and legal institution that can accommodate the implementation of REDD+ projects in Indonesia. This paper will also to conducting REDD+ national concept by doing the lessons learnt on other forest state national policy. The conclusion of this paper can provide a clear position on the implementation of REDD+ in Indonesia starting from the validity of the existing legal policies until give optional model for others countries.Keywords: climate change, legal response, mitigation